Injuries of the floating crew of the Northern water pool in a state of alcoholic intoxication - Shapovalov, Konstantin A (International maritime health, 2013)
The analysis of injuries of floating crew of the Northern water pool in a state of alcoholic intoxication havebeen based on the 180 accidents on board of ships with temporary loss of ability to work, and 1686 casehistories with alcoholic injuries, which demanded treatment in a surgical department. Among persons,the received injuries on the ship in the state of alcoholic intoxication were 8.1% of the victims: in thestrength of the transport fleet - 8.9%; fishing - 8.9% and river ones - 4.1%. Masters of fish production,skippers, rulers of the radio stations and masters of fish processing were most frequently injured afterthe consumption of the alcoholic beverages. Alcoholic injuries have been recorded at the time of walkingon the catwalk and the decks (54.2%), mooring operations (15.1%), maintenance and repairing the deckmachinery, water preparation (6.6%), as well as boat and loading-unloading works (4.3%). Falls from heightconstituted 36.6% of the injuries. Alcohol in 3.2 times increases the weight of the combined injuries. Thedeaths from the alcohol related injuries in marine conditions (43.4%) significantly exceed the indicators inthe group of non-alcoholic injuries (7.0%). Alcoholic intoxication has been noted in 35.0% of the cases ofthe floating crew injuries, hospitalised in the surgical department. Victims with alcoholic injuries receivedduring performing ship's works were hospitalised 10 times less, than those with non-productive types ofinjuries. In the structure of non-industrial injuries, household injuries prevail (78.2%) over those receiveddue to falls on the street, in pedestrian flows (10.3%), transport and traffic accidents (6.7%), intentionalinjuries (4.1%) or those connected with sports games and competitions (0.7%). Fishermen are a professionalgroup of seamen, subject to the high social vulnerability to the alcoholic beverages consumptionand related injuries.